Dezocine as a potent analgesic: overview of its pharmacological characterization - Ye Rong-Rong; Jiang Shuang; Xu Xu; Lu Yan; Wang Yu-Jun; Liu Jing-Gen (Acta Pharmacologica Sinica; Vol 43, No 7 (July 2022): Acta Pharmacologica Sinica, 2022)
Dezocine, a synthetic opioid, introduced in 1970s as an analgesic, was redeveloped for relieving moderate to severe pain by Yangtze River Pharmaceutical Group in China in 2009. To date, dezocine occupies 45% of China’s opioid analgesic market. Along with dezocine being a dominated painkiller, a certain amount of research was conducted to elucidate dezocine’s action. In this review we summarize the current knowledge on the receptor, preclinical and clinical pharmacology of dezocine. Briefly, preclinical data show that dezocine is effective under varying pain conditions, particularly chronic neuropathic pain and cancer pain, through activation of opioid receptors, and inhibition of norepinephrine reuptake. Clinical data establish the effectiveness of dezocine either as a primary analgesic for postoperative pain management or a supplement for balanced analgesia. The receptor profile of dezocine is different from known pure μ agonists, and allows it to be used in combination with other opioids for additivity in efficacy or lower incidence of adverse effects.